Integrating experimental and numerical approaches to simulate viscous debris flows using an HBP-SPH framework - Nikhil Kumar Pandey; Neelima Satyam; Benjamin Basumatary (Scientific Reports)
Abstract Accurately modeling debris flow behavior remains challenging, particularly for highly viscous flows, due to limitations in conventional rheological models and uncalibrated field data. This study integrates the Herschel-Bulkley-Papanastasiou (HBP) model with Smoothed Particle Hydrodynamics (SPH) using the DualSPHysics framework, combining numerical simulations with experimental and field investigations to improve debris flow modeling. A flume-based experimental setup was used to analyze flow initiation, velocity evolution, and deposition patterns under controlled conditions, providing crucial calibration data for the numerical model. Geotechnical and geophysical site investigations further refined key rheological parameters, ensuring accurate representation of material behavior. The calibrated model was then applied to the 2020 Pettimudi debris flow in Kerala, India, capturing key flow characteristics such as a peak velocity of 16 m/s, hydrodynamic pressures of 80–200 kPa, and a deposition width of 110 m. These predictions were validated through field surveys and historical data, demonstrating the model’s reliability in replicating real-world debris flow behavior. The study highlights the effectiveness of SPH combined with the HBP model in addressing limitations in traditional methods, providing a flexible and scalable framework for simulating debris flows. The methodology offers valuable insights into flow mechanics and has significant potential for hazard assessment, mitigation planning, and back-analysis of past debris flows in vulnerable regions worldwide This study highlights the novelty of integrating experimental, numerical, and field-based approaches to improve debris flow modeling. The findings demonstrate that SPH, combined with the HBP model, provides a flexible framework for simulating viscous debris flows, addressing limitations in traditional methods.